Synthesis and Crystal Structure of Di(thiocyanato-kN) bis(1,10-phenanthroline-5,6- dione-k2N,N’) Cadmium(II): [Cd(C12H6N2O2)2(H2O)2]·(ClO4)2·(H2O) - Liu, Xia; Hu, Da-Hua (Asian Journal of Chemistry, 2010)
A novel 3D supramolecular complex di(thiocyanato- kN)bis(1,10-phenanthroline-5,6-dione- k2N,N') cadmium(II) synthesized with a formula as [(C12H6N2O2)2Cd(H2O)2]·(ClO4)2·(H2O), was synthesized by 1,10-phenanthroline-5,6-dione and Cd(ClO4)2. In the crystal structure of the present complex, cadmium ion located in a six-coordinated environments with a distorted octahedral geometry. The intermolecular hydrogen bonds interactions among the near mononuclear units are playing an important role in the construction of 3D-superamolecular network. The crystal is monoclinic, space group P21/c with unit cell parameters: a = 16.027(2) Å, b = 13.0521(17)Å, c = 15.365(2)Å, a = 90º, b = 115.889(2)º, g = 90º, V = 2891.6(6)Å3, Z = 4, Mr = 785.73, Dc = 1.805 g/cm3, μ = 1.022 mm-1, F(000) = 1568, R = 0.0532, wR = 0.1731 for 6317 reflections with I > 2s(I).